ATMOSPHERIC MODELS FOR USE IN HYDRODYNAMIC COMPUTER CODES - Brackbill, Jeremiah U.; Nawrocki, Edmund A.; Whitaker, William A. (1967)
A hydrostatically stable atmospheric model is necessary to perform theoretical calculations of hydrodynamic motion in the atmosphere, on a digital computer. This report presents three such models developed at the Air Force Weapons Laboratory for use in its hydrodynamic computer codes. One is for the annual mean temperate atmosphere (45 deg N latitude); one for the annual mean tropical atmosphere (15 deg N latitude); and one for the summer subarctic atmosphere (60 deg N latitude). The models are presented herein in tabular form and as FORTRAN subroutines which could be placed directly into any hydrodynamic computer code. For a given altitude (cm), the subroutines return a pressure (dynes/sq cm), density (gms/cu cm), specific internal energy (ergs/gm), temperature (degrees K), and gamma - 1). The pressures and densities agree with tabulated values to at least 1 part in 10 to the 8th power and temperatures to at least 1 part in 100. The atmospheres experience an acceleration of no more than 3 parts in 1000 in a first order finite difference scheme with a zone size of 1 kilometer, the worst case.